К ВОПРОСУ О ГЕНЕЗИСЕ ЛОЖБИН СТОКА ЮГО-ВОСТОКА ЗАПАДНО-СИБИРСКОЙ РАВНИНЫ - Евсеева Н.С. (My University, 2005)
The tectonic origin of the crest-hollow topography at the South-East of West Siberia was set. The high quantity of bogs and lakes in the hollows are explained by their closeness to fault zones.
Keywords: 551.435.1(571.1)